2021
DOI: 10.1017/s0714980821000039
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Communication Breakdowns during Emergency Care Transitions of Older Adults: Evaluation of a Standardized Inter-Facility Health Care Communication Form

Abstract: Transitions for older persons from long-term care (LTC) to the emergency department (ED) and back, can result in adverse events. Effective communication among care settings is required to ensure continuity of care. We implemented a standardized form for improving consistency of documentation during LTC to ED transitions of residents 65 years of age or older, via emergency medical services (EMS), and back. Data on form use and form completion were collected through chart review. Practitioners’ perspectives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The authors of three studies evaluated healthcare professionals’ perspectives on whether using standardized documentation forms improved their understanding of patient needs and ability to care for patients ( Madden et al, 1998 ), and also assessed form uptake ( Belfrage et al, 2009 ; McLane et al, 2022 ) and item completion ( McLane et al, 2022 ; Terrell et al, 2005 ). Belfrage et al (2009) reported that form uptake was high (89%) for eligible cases, whereas McLane et al (2022) reported lower form uptake (43%; McLane et al, 2022 ). Item completion improved or was perceived to have improved (by RACF, emergency medical services [EMS], and ED staff) in both studies ( McLane et al, 2022 ; Terrell et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors of three studies evaluated healthcare professionals’ perspectives on whether using standardized documentation forms improved their understanding of patient needs and ability to care for patients ( Madden et al, 1998 ), and also assessed form uptake ( Belfrage et al, 2009 ; McLane et al, 2022 ) and item completion ( McLane et al, 2022 ; Terrell et al, 2005 ). Belfrage et al (2009) reported that form uptake was high (89%) for eligible cases, whereas McLane et al (2022) reported lower form uptake (43%; McLane et al, 2022 ). Item completion improved or was perceived to have improved (by RACF, emergency medical services [EMS], and ED staff) in both studies ( McLane et al, 2022 ; Terrell et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“… Belfrage et al (2009) reported that form uptake was high (89%) for eligible cases, whereas McLane et al (2022) reported lower form uptake (43%; McLane et al, 2022 ). Item completion improved or was perceived to have improved (by RACF, emergency medical services [EMS], and ED staff) in both studies ( McLane et al, 2022 ; Terrell et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations